A produção de conhecimento e a ambientação na atividade de formação de professor - Schneider, Márcia Sueli Pereira da Silva (2008)
This research aims to discuss the teacher formation and verify how the knowledge is produced during the formation process developed in two settings: in a face-to-face environment and in a distance setting. In this way, this work chose as base for the research a continued professional development project, based on the relations between the researcher and an English teacher that worked at Basic Level I in a Municipal School in Conceição dos Ouros-MG. As foundation to the discussions this work is based on Socio-Historical-Cultural Activity Theory (TASHC) (Vygotsky, 1934/2001, 1999, 1998; Leont ev,1959, 1978; Engeström, 1987, 1999, 2006 and others), on the discussion about on line setting to understand the settings supplied by Computer Mediated Communication and its movements that take to the virtualization, founded, principally, in Levy s (1996/2003; 1999/2003) works. Regarding the critical reflective principles, the study is based on the studies developed by Freire (1979/2001), Brookfield & Preskill (1999), Liberali (2005, 2004), Brookfield (1987), Smyth (1989), and others, and in the language role mediating the social inter-relations that has the argumentation as an important allied to the development of the critical reflective thought. This research is inserted in a critical collaborative perspective (Comstock, 1982, Bredo & Feinberg, 1982, Magalhães, 1992, 1994, 1998, no prelo), since it is an investigative process that aims to observing, analyzing and transforming the educational practices of the participants. Parts of face-to-face and distance conversation, of reflective diary and reflections developed in an email setting were selected and analyzed. The intention of analyzing the cutting data was to understand how sense about teaching-learning was questioning and new meanings were shared during the teacher formation activity on the environments used. The results show that knowledge production happens when there are opportunities to the participants manifest themselves, expounding their opinions, to agree or disagree, to listen and to be listened, opportunity to argue and to convince the others, learning, this way, to interact with respectful by others. In this social production process, the role of the other becomes fundamental to trigger off news ZPDs, to reorganize and transform the senses and to develop. The results show as well that the virtual setting allows that the teacher formation activity was updated, become real in a virtual setting, and that the asynchronous communication turned out to be more formal than the synchronous communication that was characterized by an interaction similar as a face-to-face interaction